Antibacterial and Antibiofilm Activity of Mercaptophenol Functionalized-Gold Nanorods Against a Clinical Isolate of Methicillin-Resistant Staphylococcus aureus - Nahla O. Eltai (9291053) (2022)
Gold nanorods (AuNRs) were synthesized by the seed-mediated wet chemical method using a binary surfactant system. AuNRs were stabilized with polyethylene glycol, then functionalized with 4-mercaptophenol (4-MPH) ligand by surface ligand exchange. The surface-functionalized AuNRs (4-MPH-AuNRs) exhibited a typical UV–vis spectrum of AuNRs with a slightly shifted longitudinal peak. Furthermore, 4-MPH-AuNRs demonstrated a similar Fourier-Transformed Infrared spectrum to 4-MPH and a fading of the thiol band, which suggests a successful functionalization through thiol-gold binding. The antibacterial and antibiofilm activities of 4-MPH-AuNRs were evaluated against a clinical isolate of Methicillin-Resistant Staphylococcus aureus (MRSA). The results indicate that 4-MPH-AuNRs exhibit a bactericidal activity with a minimum inhibitory concentration (MIC) of ~ 6.25 $$\upmu$$ μ g/mL against a planktonic suspension of MRSA. Furthermore, 4-MPH-AuNRs resulted in a 1.8–2.9 log-cycle reduction of MRSA biofilm viable count over a concentration range of 100–6.0 $$\upmu$$ μ g/mL. The bacterial uptake of the surface-modified nanorods was investigated by inductively coupled plasma-optical emission spectroscopy (ICP-OES) and scanning electron microscopy (SEM) imaging; the results reveal that the nanorods were internalized into the bacterial cells after 6 h (h) of exposure. SEM imaging revealed a significant accumulation of the nanorods at the bacterial cell wall and a possible cellular internalization. Thus, 4-MPH-AuNRs can be considered a potential antibacterial agent, particularly against MRSA strain biofilms. Other Information Published in: Journal of Inorganic and Organometallic Polymers and Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10904-022-02294-0